Efficient and selective carbon dioxide reduction on low cost protected Cu2O photocathodes using a molecular catalyst1. Issue 3 (5th March 2015) - Schreier, Marcel; Gao, Peng; Mayer, Matthew T.; Luo, Jingshan; Moehl, Thomas; Nazeeruddin, Mohammad K.; Tilley, S. David; Grätzel, Michael
<x xml:space="preserve">Abstract</x> A TiO2-protected Cu2O photocathode was paired with a molecular catalyst to drive the efficient and selective reduction of CO2 to CO.